Edukasi “Menjaga Iman dan Hati” Dalam Bermedia Sosial di Era Digital - Afdin, Ardianti; Rahmawati; Fitri Ruqoyah; Rita Putri Oktaviani; Lefince Laratmase; Siti Kurnita Alifa; Lira; Falerida Basaria Sinaga; Syalsabila Ramdayanti Saputri; Sujono Riyadi (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
This activity represents a form of educational philanthropy implemented as part of the Tri Dharma of higher education and documented in this publication. Grade VII students at SMP Negeri 1 Gamping, as partners, face significant challenges with social media use in the digital era, including excessive addiction that disrupts academic performance, exposure to negative content eroding religious values and faith, rampant cyberbullying, and vulnerability to hoaxes and misinformation that foster unethical behavior. The objective is to enhance students' understanding of social media ethics and impacts while upholding religious values and faith. The implementation method employed an interactive lecture approach and discussion sessions with the implementation team (academic colleagues). Evaluations were conducted informally through observations of active participation and verbal question-and-answer sessions at the beginning and end of the activity. Results showed positive responses and high enthusiasm from students. Although lacking formal quantitative measurements (pretest-posttest), the activity was deemed successful in significantly boosting students' awareness and insights into the importance of wise and ethical social media behavior.